2011
DOI: 10.1038/emboj.2011.151
|View full text |Cite
|
Sign up to set email alerts
|

AP-2γ regulates oestrogen receptor-mediated long-range chromatin interaction and gene transcription

Abstract: Oestrogen receptor a (ERa) is key player in the progression of breast cancer. Recently, the cistrome and interactome of ERa were mapped in breast cancer cells, revealing the importance of spatial organization in oestrogenmediated transcription. However, the underlying mechanism of this process is unclear. Here, we show that ERa binding sites (ERBS) identified from the Chromatin Interaction Analysis-Paired End DiTag of ERa are enriched for AP-2 motifs. We demonstrate the transcription factor, AP-2c, which has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 50 publications
10
117
1
Order By: Relevance
“…In addition, these genome-wide studies also showed that additional transcription factors are required for the accurate targeting of ER onto cognate sequences along the whole genome (16). These factors include FOXA1 (17), TFAP2C (18), and PBX1 (19). Among those, FOXA1 may act as an allosteric sensor for histone marks associated with active or poised chromatin (such as H3K4 mono-or dimethylation), and it is therefore considered a pioneer factor preparing chromatin for subsequent binding of ER (20)(21)(22).…”
mentioning
confidence: 99%
“…In addition, these genome-wide studies also showed that additional transcription factors are required for the accurate targeting of ER onto cognate sequences along the whole genome (16). These factors include FOXA1 (17), TFAP2C (18), and PBX1 (19). Among those, FOXA1 may act as an allosteric sensor for histone marks associated with active or poised chromatin (such as H3K4 mono-or dimethylation), and it is therefore considered a pioneer factor preparing chromatin for subsequent binding of ER (20)(21)(22).…”
mentioning
confidence: 99%
“…Genome-wide analysis of ARBS also revealed that only a small portion of binding sites contains the canonical class I NR motif (5 0 -AGAACANNNTGTTCT-3 0 , allowing up to two positions to vary from the palindromic consensus with three nt spacing) (Verrijdt et al 2003), whereas most sites contain only a half-site of the ARE . This is in contrast to other NRs such as estrogen receptor a and peroxisome proliferator-activated receptor g, whose binding sites predominantly contain their cognate consensus response elements (Lin et al 2007, Nielsen et al 2008, Welboren et al 2009, Tan et al 2011. The low occurrence of canonical AREs at ARBS suggests that the binding of AR to chromatin is likely dependent on additional transcription factors.…”
Section: Ar Co-regulatory Networkmentioning
confidence: 67%
“…More recently, this same approach has been used to identify other putative pioneer factors for ERα, including PBX1 that can guide ERα to a specific subset of sites (Magnani et al 2011). When investigating the motifs of ERα-bindings sites identified by ChIA-PET, Tan and coworkers found that approximately 40% of these binding sites contained the AP-2 motif (Tan et al 2011). They next demonstrated that transcription factor AP-2γ can bind to these ERα-bindings sites in a ligand-independent manner and there is a functional interplay between AP-2γ and FOXA1 (Tan et al 2011).…”
Section: Erα Cistromics In Breast Cancer Cell Linesmentioning
confidence: 99%
“…Initial ChIP-on-chip experiments have shown ERα to mainly bind enhancer regions (Carroll et al 2005). Computational DNA sequence motif analyses of ERα-binding sites resulted in the identification of a number of upstream transcription factors that facilitate the binding of ERα to the chromatin, including pioneer factor FOXA1 (Carroll et al 2005, Hurtado et al 2011 and putative pioneer factors PBX1 (Magnani et al 2011) and AP-2γ (Tan et al 2011) (Fig. 1).…”
Section: Er Complex Formation and Its Mode Of Actionmentioning
confidence: 99%